Perbaikan Kestabilan Dinamik Pada Sistem Tenaga Menggunakan Kontrol Gain Avr Pss - Wahyuni Martiningsih; Inawati Inawati; Heri Haryanto (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2014)
The stability of the electric power system is very important, because the stability of the system affects the quality and reliability of electrical energy supply. Many things can affect the stability of the system, one of which is a dynamic load that affects dynamic stability, dynamic stability can be defined as the system's ability to remain in synchronous conditions after the first swing (transient period) until the system reaches steady state condition, a power system is said to be in stable when all variables are stable, both bus voltage, rotor angle and generator rotor rotational speed. In this study the authors used the automatic voltage regulator (AVR) and power system stabilizer (PSS) controls to control the system's dynamic stability, hoping that after installation of these additional control devices the dynamic stability of the power system could be improved so that the system remained stable despite disturbances or load changes . Then a power system simulation was carried out using the MATLAB 2008a program, which proved that the installation of a power system stabilizer can reduce oscillation, in this case PSS works as an electric power controller or reactive power can be seen from the output voltage which only has overshoot 1.0169 before a load change and after being given a load change with the input step 25 overshoot increasing only 1.0215 for output the speed and angle of the generator rotor is less influential.